Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Supposing I have a matrix, $\pmatrix{0&0&\lambda\\0&\lambda&-1\\ \lambda&-1&0}$.

Without question you can work out the inverse if this matrix. But since it is highly structured, I suppose there should be some quick way to find out the inverse of it?

Can anyone show me a quick way of thinking about this problem?

share|cite|improve this question
thank you Henning for your help on editing it. – SoManyProb_for_a_broken_heart. Nov 4 '11 at 2:09
[retracted unfair comment] – user16299 Nov 4 '11 at 3:48
up vote 8 down vote accepted

The determinant of the matrix is easily seen to be $-\lambda^3$, so Cramer's formula will quickly invert it.

If I've got all of the minors correct, it should be $$A^{-1}=\frac{-1}{\lambda^3}\pmatrix{-1&-\lambda&-\lambda^2\\ -\lambda&-\lambda^2&0 \\ -\lambda^2&0&0}$$

share|cite|improve this answer

Let $A$ be your matrix. Then $J=\pmatrix{0&0&-1\\0&-1&0\\ -1&0&0}A$ (switching the first and third rows and switching signs) is the Jordan block with $-\lambda$ on the diagonal. You can take the inverse of Jordan blocks using the approach shown in this Wikipedia article on matrix functions. This yields $J^{-1}=\pmatrix{\frac{-1}{\lambda}&\frac{-1}{\lambda^2}&\frac{-1}{\lambda^3}\\0&\frac{-1}{\lambda}&\frac{-1}{\lambda^2}\\ 0&0&\frac{-1}{\lambda}}$, simply by evaluating $f(-\lambda)$, $f'(-\lambda)$, and $f''(-\lambda)$, where $f(x)=\frac{1}{x}$. Then note that $A^{-1}=J^{-1}\pmatrix{0&0&-1\\0&-1&0\\ -1&0&0}$, so you switch the first and third columns and switch signs again to get the same result as percusse.

share|cite|improve this answer

I would have done with a detour: Call the original matrix $A$, we can spot with a permutation matrix $P$ that $$ PA = \pmatrix{&&1\\&1&\\1&&}A = \pmatrix{\lambda&-1&0\\ 0&\lambda&-1\\ 0&0&\lambda} =: B $$ Inverse of this Jordan-like upper triangular $B$ is slightly easier but admittedly requires some affinity: (See Jonas' answer for detailed version) $$ B^{-1} = \left(\begin{array}{ccc} \frac{1}{\mathrm{\lambda}} & \frac{1}{{\mathrm{\lambda}}^2} & \frac{1}{{\mathrm{\lambda}}^3}\\ 0 & \frac{1}{\mathrm{\lambda}} & \frac{1}{{\mathrm{\lambda}}^2}\\ 0 & 0 & \frac{1}{\mathrm{\lambda}} \end{array}\right) $$ Finally, $$ A^{-1} = B^{-1}P = \pmatrix{\frac{1}{\lambda^3}&\frac{1}{\lambda^2}&\frac{1}{\lambda}\\\frac{1}{\lambda^2}&\frac{1}{\lambda}&0\\\frac{1}{\lambda}&0&0} $$

share|cite|improve this answer
Thanks! That is something really nice. Does " requires some affinity" means the inverse of upper triangular is upper triangular? And what do you mean by "done with a detour" here? You mean you want to change the structure of it? – SoManyProb_for_a_broken_heart. Nov 4 '11 at 2:25
@SoManyProblems Actually, everything except the matrices is wrong in my post :) it is indeed upper triangular yes! Man, I really need coffee. By detour I mean I permute it and compute the inverse and permute back. And Jonas' answer has the affinity part. I did inverse of Jordan blocks too many times that I can identify the inverses more or less correctly. That's what I meant. – user13838 Nov 4 '11 at 2:30
Note that $$B/\lambda=\pmatrix{1&-\frac{1}{\lambda}&0\\ 0&1&-\frac{1}{\lambda}\\ 0&0&1}=I-U/\lambda$$ where $U$ is the superdiagonal matrix. Since the superdiagonal matrix is nilpotent, $(I-U/\lambda)^{-1}=I+U/\lambda+U^2/\lambda^2+\dots$ converges. Thus, $$\begin{align}B^{-1}&=(B/\lambda)^{-1}/\lambda\\&=(I+U/\lambda+U^2/\lambda^2+\do‌​ts)/\lambda\\&=\pmatrix{ \frac{1}{\lambda} &\frac{1}{\lambda^2}&\frac{1}{\lambda^3}\\0&\frac{1}{\lambda}&\frac{1}{\lambda^2}‌​\\0&0&\frac{1}{\lambda}}\end{align}$$ – robjohn Nov 4 '11 at 8:46

This matrix is simple enough that we can find its inverse quite easily by simply writing out the product of it with its inverse: $$ \pmatrix{0&0&\lambda\\0&\lambda&-1\\ \lambda&-1&0} \pmatrix{a_{11}&a_{12}&a_{13}\\a_{21}&a_{22}&a_{23}\\ a_{31}&a_{32}&a_{33}} = \pmatrix{1&0&0\\0&1&0\\ 0&0&1} $$ Taking the first row and first column product, $0a_{11}+0a_{21}+\lambda a_{31} = 1$, so $a_{31} = 1/\lambda$. Now the second row and first column gives us $0a_{11}+\lambda a_{21}+-1/\lambda = 0$, so $a_{21} = 1/\lambda^2$ ... and so on for the rest of the matrix.

share|cite|improve this answer
Thank you discipulus! – SoManyProb_for_a_broken_heart. Nov 4 '11 at 2:40

You can partition the matrix into $$ \begin{bmatrix} 0 & v^\top \\ v & A \end{bmatrix} $$ where $A$ is a symmetric $2\times2$ matrix and $v$ a $2\times1$ vector, yielding the solution of $$ \begin{bmatrix} 0 & v^\top \\ v & A \end{bmatrix}^{-1} = \begin{bmatrix} -(v^\top A^{-1} v)^{-1} & T^\top \\ T & A^{-1}-T v^\top A^{-1} \end{bmatrix} $$ where $T = A^{-1} v (v^\top A^{-1} v)^{-1} $ is the weighted pseudo inverse of $v$, since $T^\top v=1$ and $v^\top T=1 $

Proof: $$ \begin{bmatrix} -(v^\top A^{-1} v)^{-1} & T^\top \\ T & A^{-1}-T v^\top A^{-1} \end{bmatrix} \begin{bmatrix} 0 & v^\top \\ v & A \end{bmatrix} = \begin{bmatrix} T^\top v & -(v^\top A^{-1} v)^{-1} v^\top+T^\top A \\ A^{-1}v-T v^\top A^{-1} v & T v^\top + A^{-1} A - T v^\top \end{bmatrix} $$

with the simplification $T^\top A = (v^\top A^{-1} v)^{-1} v^\top$ the above becomes

$ \begin{bmatrix} 1 & 0 \\ 0 & 1 \end{bmatrix} $


$A = \begin{pmatrix} \lambda & -1 \\ -1 & 0 \end{pmatrix} $, $v = \begin{pmatrix} 0 \\ \lambda \end{pmatrix}$, $T = \begin{pmatrix} \lambda & -1 \\ -1 & 0 \end{pmatrix}^{-1} \begin{pmatrix} 0 \\ \lambda \end{pmatrix} \left(\begin{pmatrix} 0 & \lambda \end{pmatrix} \begin{pmatrix} \lambda & -1 \\ -1 & 0 \end{pmatrix}^{-1} \begin{pmatrix} 0 \\ \lambda \end{pmatrix} \right)^{-1} = \begin{pmatrix} \frac{1}{\lambda^2} \\ \frac{1}{\lambda} \end{pmatrix}$

$$ \begin{bmatrix} -(v^\top A^{-1} v)^{-1} & T^\top \\ T & A^{-1}-T v^\top A^{-1} \end{bmatrix} = \begin{bmatrix} \begin{pmatrix} \frac{1}{\lambda^3} \end{pmatrix} & \begin{pmatrix} \frac{1}{\lambda^2} & \frac{1}{\lambda} \end{pmatrix} \\ \begin{pmatrix} \frac{1}{\lambda^2} \\ \frac{1}{\lambda} \end{pmatrix} & \begin{pmatrix} \frac{1}{\lambda} & 0 \\ 0 & 0 \end{pmatrix} \end{bmatrix} $$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.